XIX. yüzyıla kadar olan mevlevi ayinlerinde usül-vezin ilişkisi - İlhan, Ayşe Başak (My University, 2006)
Arap orijinli aruzun, örf, âdet ve geleneklerin sembolleştirdiği Arap dili semantiğinin ritmik ve îkaî bulmaca benzeri bir îcadı olması (El Halil), buna bağlı olarak yine aynı çadır kültürü geleneğinden hareketle, müzikte (ritmik jimlastik denebilecek bir yolla) “Ten, nen, te-nen, ten-ni ...” gibi ikâî kalıplar kullanarak şiirmûsikî ilişkisinin ortaya konulduğu kabul edilebilir. Terennüm adıyla Klâsik Türk Mûsikîsi’nde kullanılan bu unsurlar aruz vezni ile birlikte benimsenen müzik kalıpları olmuşlardır. Dolayısı ile aynı yolla (bir çeşit onomatopei “tabiî seslerin taklidinden yapılmış kelime” ile) elde edilen ve müzikteki usûlü meydana getiren kuvvetli-zayıf, uzun-kısa darpların ( Düm, tek, te-ke, tek-kâ ...), terennümlerle ve aruzun tef’ileleri ile organik bağı şüphe götürmez bir durumdadır. Özellikle sözlü müzik besteciliğinde usûl-vezin ilişkisi, karşımıza bu vecheyle çıkar. Zamanla gelişen estetik zevk ve buna bağlı olarak yaygın kullanım kazanan Türk Aruzu kendine uygun usûllerin tercihinde başlıca rolü oynamıştır. Aynen aruzdaki tef’ilelerin değişik kombinasyonlarının bir arada kullanılması sonucu vezinlerin ortaya çıkması ve tercih edilir olmaları gibi farklı usûl düzümlerinin de değişik kombinasyonlarla birleşmeleri sonucu yine kuvvetle tercih edilen usûl îka’larının ortaya çıkmış olmasıdır. Usûl-vezin ilişkisinin elde edilmiş en bâriz sonucu da budur. Semâ kıyâmî (ayakta), devrânî (dönerek) ve hafî (sessiz) yapılan Mevleviyye tarîkatına özgü bir zikir türüdür. Mûsîki, semâ‘ın ayrılmaz bir parçasıdır. Mevlânâ ve ondan sonraki ilk çelebiler döneminde, sonradan mukābele adı verilecek törende, buna eşlik edecek özel olarak bestelenmiş eserler de yoktu. Semâ‘, mukābele şeklini aldıktan sonra Mevlevî âyin-i şerîfi bir mûsikî formu olarak ortaya çıkmaya başladı. Bu formun ilk örnekleri bestekârı bilinmediğinden “Beste-i Kadîm” adını almış olan pençgâh, dügâh ve hüseynî âyinleridir. XIX. yüzyıla kadar ondokuz Mevlevî âyini bestelenmiş, bunlardan onbeşi günümüze ulaşabilmiştir. Bu çalışmada XIX. yy.’a kadar bestelenmiş onbeş Mevlevî âyinini usûl ve vezin ilişkileri açısından incelenmiştir. ix Çalışma üç bölümden oluşmaktadır. Birinci bölümde Mevlevî Âyîn-i Şerîfi, Mevlevî âyinlerinde yapı, Mevlevî âyînlerinin usûl özellikleri, güfte özellikleri ve beste ve makam özellikleri üzerine açıklayıcı bilgi verilmiştir. İkinci Bölümde XIX. yüzyıla kadar bestelenmiş Mevlevî Âyinleri notalarıyla birlikte verilerek, her âyin kendi içinde selâmlara göre usûl-vezin ilişkileri tablolarla geniş biçimde ele alınmıştır. Değerlendirme ve Sonuç bölümlerinde ise XIX. yüzyıla kadar bestelenmiş Mevlevî âyinlerindeki selâmların usûl-vezin ilişkisi açısından karşılaştırmalı değerlendirmesi yapılmıştır.

Turkish Literature and Music underwent a critical change in the period after the Turks accepted Islam due to the Aruz meter (poetic prosodic meter). However a long time elapsed after their first contact with Arabic and Persian Aruz, before Aruz was utilized. This can be verified by the fact that the first known metered poetic verses contained undevloped metric errors and that these meters were later abandoned. Independent of Arabic and Persian Aruz, Turkish Aruz brought to our poetry an aestheic taste which together with music evolved over time in a manner allowing it to reach its peak. Aruz which is of Arabic origin, appears to have been created like a rythmic and îkaî (verbal) puzzle of semantics of the Arabic language symbolizing their customs and traditions (El Halil), and thus it can be considered that the relationship between poetry and music also sprang from this same nomadic cultural tradition using verbal patterns (ikâî terennüms) like “Ten, nen, te-nen, ten-ni …” in music (in a manner akin to that of rythmic gymnastics). Under the name of terennüm (extra-lyric verbal embellishments) these elements were utilized in Classical Turkish Music together with the Aruz meter in accepted musical patterns. Therefore, there is no doubt that in a similar manner (with a kind of onomatopoeia (words made by copying natural sounds) the usûl (rythmic pattern) in music was obtained and came about from the strong-weak and long-short beats (Düm, tek, te-ke, tek-kâ...) and that there is an organic connection between terennüms and the Aruz tef’iles (word patterns of aruz). We especially come across this point of view in the relationship between usûl (rythmic pattern) and vezin (prosodic meter) in the composing of vocal music. The aesthetic taste which developed over time and with this the gaining of its widespread usage played a major role in the choice of especially appropriate usûls for Turkish Aruz. Just as the utilization of different combinations of tef’iles (word patterns of aruz) together resulted in the appearance of the vezins and their becoming preferable, in the same manner the different düzüms (rhytymic combinations) of various combinations and mergings resulted again in strongly preferred usûl îka’s (cyclical rythmic patterns) being created. This is the most obvious conclusion that has been 2 gained from the usûl-vezin (concordance of prosodic and musical meters) relationship. Sema is a kind of dhikr made by whirling, standing with silence. During the period of Mevlânâ and his first followers, there were no composed works which was called afterwards mukabele. As soon as sema has taken the shape of mukabele, Mevlevî âyini began to come into picture as a musical form. The most beautiful samples of this form are pençgâh, dügâh and hüseynî âyins which were called beste-i kadim because of their unknown composers. Until 19th century, 19 mevlevî âyins had been composed and only 15 had been managed to reach this time. In this thesis, the Mevlevî âyins which took place until 19th century and their concordance between musical and poetic meters had been analyzed. This thesis includes three chapters. In the first chapter, the information related to Mevlevî âyins, the form of Mevlevî âyins, ritmic, poetic and musical features of Mevlevî âyins has been given. In the second chapter, 15 Mevlevî âyins have been examined with their score and each akin has been taken on according to their selams. The concordance between rhythmic and poetic meters has been indicated by some tables. In the conclusion chapter, comparative evaluation of 15 Mevlevî âyins has been discussed according to their concordance between rhythmic and poetic meters.
Keywords: İslam Tarihi; Mevleviler; Tasavvuf Müziği